An Unusual Presentation of Neuronal Ceroid Lipofuscinosis With CLN6 Mutation - Shahin Koohmanaee; Seyyedeh Azadeh Hoseini Nouri; Vahid Aminzadeh; Manijeh Tabrizi; Reza Bayat; Fatemeh Kharaee; Maryam Shahrokhi; Afagh Hassanzadeh Rad; Saber Najafi Chakoosari; Setila Dalili; Ehsan Kazemnejad Leili (Caspian Journal of Neurological Sciences, 2023)
Background: Neuronal ceroid lipofuscinoses (NCL) is a rare progressive neurodegenerative disorder caused by more than 530 mutations of at least 13 different genes (CLN 1-14). NCL is a part of the lysosomal disease characterized by the presence of neuronal and extraneural autofluorescent lipopigment accumulations that leads to motor and mental deterioration, developmental regression, seizure, vision loss, and premature death. NCL is classified into four main groups based on the different clinical manifestations and age of presentation. In this study, we aimed to report an unusual presentation of NCL with CLN6 mutation without retina involvement. Case Presentation: We reported a 10-year-old boy with mixed types of seizures, developmental delay, cognitive problems, unsteady gait, and speech disorders. Although after a thorough assessment, CLN6 mutation was diagnosed, he had all symptoms of this mutation, except the visual impairment. Conclusion: According to recent NCL case reports from Asia, full familiarity with its presentation by pediatricians and neurologists is obligatory. Children with developmental regression or refractory seizures, who also have visual or other neurological symptoms such as ataxia and other cerebellar symptoms, even at older ages, should be evaluated for NCL. Attention to ophthalmological examinations and neurological signs and confirming the diagnosis by biopsy or genetic analysis is desirable to prevent missed diagnosis.